A Three-Dimensional Analytical Study of the Spike Skill in Volleyball According to Certain Biomechanical Motion Variables and Performance Technique Among the University of Tikrit Team Players - Wissam Awni Saleh; Wissam Mahdi Saleh; Osama Lotfi Jassim (Pubmedia Jurnal Pendidikan Olahraga, 2025)
This research aimed to analyze the biomechanical and technical variables related to performance and to assess the efficiency and effectiveness of the smashing skill among volleyball players from Tikrit University. The researchers hypothesized that three-dimensional kinematic analysis could help identify specific kinematic variables and evaluate the efficiency of the smashing technique used by these athletes. To achieve this, the researchers adopted a descriptive approach utilizing the case study method, which was deemed most suitable for examining the biomechanical and technical elements of the smashing skill. The research sample consisted of four intentionally selected players from the Tikrit University volleyball team, all of whom participated in the Iraqi Universities Championship during the 2023–2024 academic year. These players were chosen specifically for their specialization in smashing, aligning with the study’s objectives. The findings revealed that allocating the appropriate amount of time for performing a smash significantly enhances performance, with players who minimize execution time proving more effective in offensive play. Additionally, variations in the body’s center of gravity were found to influence performance levels; players with a higher center of gravity are better positioned to reach higher points, thereby increasing their potential for delivering powerful and well-timed smashes. Based on these conclusions, the researchers recommended focusing on improving the timing of the smash by training athletes to increase the speed of coordination between the pass and the smash. Furthermore, emphasis should be placed on refining jump timing and faster positioning, especially for players who currently exhibit slower execution